2016
DOI: 10.2214/ajr.15.15083
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sequential PET/MRI in Comparison With PET/CT of Pediatric Lymphoma: A Prospective Study

Abstract: In a pediatric cohort with lymphoma, sequential PET/MRI showed lesion detection, lesion classification, and Ann Arbor staging comparable to PET/CT. PET/MRI quantification of FDG uptake strongly correlated with PET/CT, but the SUVs were not interchangeable. PET/MRI significantly reduced radiation exposure and is a promising new alternative in the care of pediatric lymphoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 27 publications
1
37
0
7
Order By: Relevance
“…The initial phase of adoption focused on clinical feasibility and the degree to which it was equivalent to PET/CT for detecting lesions. In the following years, PET/MRI developed to a stage where it is superior to PET/CT for some malignancies [17,18] and has evolved into non-oncologic clinical applications such as assessment of neurodegenerative diseases. However, cultural and historical obstacles remain in the routine clinical adoption of PET/MR imaging.…”
Section: Resultsmentioning
confidence: 99%
“…The initial phase of adoption focused on clinical feasibility and the degree to which it was equivalent to PET/CT for detecting lesions. In the following years, PET/MRI developed to a stage where it is superior to PET/CT for some malignancies [17,18] and has evolved into non-oncologic clinical applications such as assessment of neurodegenerative diseases. However, cultural and historical obstacles remain in the routine clinical adoption of PET/MR imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the sometimes large differences between uptake times, most studies came to the conclusion that there was a high positive correlation for all SUV quantification metrics between both exams and that most of the differences were due to the variance in uptake time between both scans [44-48, 50, 51, 53, 54, 57, 59-61, 64]. In only two studies, some scans were performed on the PET/MR scanner first [52,58], and in two studies, all PET/MR scans were performed before PET/CT [49,56]. All other studies had a longer uptake time of 51-120 min (mean 81 min) for the PET/MR scans and showed a slight increase in SUV between both exams.…”
Section: Clinical Studies Comparing Suv Measurements Between Pet/ct Amentioning
confidence: 99%
“…Lenfomada kemik iliği infiltrasyonunun araştırılmasında ve akciğer parankiminin değerlendirilmesinde entegre PET/MR görüntülemede STIR sekansından yararlanılabilir (32). Ayrıca difüzyon ağırlıklı MR görüntülemenin hücre yoğunluğuna ilişkin sağladığı bilgiler glukoz metabolizması ile birlikte tedavi yanıtının erken dönemde değerlendirilmesi bakımından avantaj sağlayabilir (33,34). Lenfomada tedavi sonrası erken dönem değerlendirmede PET görüntülemenin sağladığı metabolik bilginin yüksek öngörü değeri taşıması, MR görüntülemenin ise karaciğer, dalak ve kemik iliği infiltrasyonlarının gösterilmesindeki üstünlüğü nedeniyle, tedavi sonrası tekrarlayan izlem çalışmalarında hastanın maruz kaldığı birikimli radyasyon dozunu azaltmak için PET/MR'ın PET/BT yerine kullanılabilir (32,33,34).…”
Section: Hematolojikmalignitelerunclassified
“…Pediatrik hastalarda yağ dokusu daha az olduğundan yumuşak doku lezyonlarının normal dokulardan ayırt edilebilirliği PET/BT sistemlerinde zor olabilir. MR görüntülemenin sahip olduğu yüksek yumuşak doku kontrastı nedeniyle bu durum pediatrik yaş grubunda PET/MR görüntülemenin tercih edilmesi için başka bir gerekçe oluşturur (5,6,8,9,33,34,35,36). Özellikle pediatrik yaş grubunda sık olarak gözlenen yumuşak doku ve santral sinir sistemi tümörlerinin ve kemik iliği tutulumlarının değerlendirilmesi bakımından PET/MR sistemi PET/ BT'ye üstünlük sağlayabilir.…”
Section: Pediatrikonkolojiunclassified